Implementasi Peralatan X-Ray sebagai Media Praktik dalam Pembelajaran untuk Meningkatkan Kompetensi Mahasiswa - Minulya Eska Nugraha; Dwi Candra Yuniar; Ahmad Hariri; Bambang Wijaya Putra; Herlina Febiyanti; Zusnita Hermala; Iwansyah Putra (Lembaga Bale Literasi, 2025)
This study aims to analyse the effectiveness of using X-ray equipment as a practical media in improving the competence of students of the Airport Management Study Program. The research method uses a qualitative approach. This research was conducted at the Airport Management Study Programme, MBU 04 class. This research involved lecturers and students. The research subjects were selected using purposive sampling technique according to data needs. Data collection was conducted through three techniques, namely observation, interview, and documentation study. To analyse the data, this study adopted the Miles and Huberman model which includes four stages, namely data collection, data reduction, data presentation, and conclusion drawing. The results showed that the use of X-ray equipment can improve students' theoretical understanding and practical skills in terms of baggage security checks. Lecturers and students stated that hands-on practice with X-ray helped understand real airport security procedures. However, the study also identified some obstacles such as the limited number of equipment and the need for technological updates to adapt to modern airport standards that already use CT Scan systems and AI-based detection. The conclusion of this study is that X-ray equipment as a practical medium in learning can improve student competence.